Stability of mechanical properties of molecular layer–deposited alucone. (December 2018) - Ruoho, M.; Tarasiuk, N.; Rohbeck, N.; Kapusta, C.; Michler, J.; Utke, I.
Abstract: We report on the effect of aging on the mechanical properties of molecular layer–deposited (MLD) thin films. We studied the mechanical failure of the films during uniaxial tensile testing and observed a sixfold difference in the crack-onset strain (COS) and related flexibility within the first two days after the samples were exposed to ambient air. The MLD films made using trimethylaluminum and ethylene glycol are notorious for exhibiting structural changes after the fabrication; we show that these changes are detrimental for mechanical robustness of the films. This information aids to plan the handling or the protection of these films to achieve better performance with these materials. The interfacial shear strains and COSs of the shortly air-exposed 300-nm-thick films were observed to be roughly 0.3% and 1.8%, respectively. These values are the highest reported so far for hybrid organic–inorganic MLD thin films and would extrapolate to about 14% COS for 5-nm-thick film, indicating potential applications as interfacial adhesion layer for films on polymer substrates and as a protective coating in battery applications. Graphical abstract: Highlights: Effect of aging in ambient air on mechanical failure of MLD alucone during uniaxial tensile testing are studied. At least a sixfold decrease in the crack-onset strain and flexibility was observed within the first two days. Cohesive film strength and interfacial shear strength had a similar trend. The elastic modulus and hardness do not change significantly.